The global gene expression profile of the secondary transition during pancreatic development. (February 2016) - Willmann, Stefanie J.; Mueller, Nikola S.; Engert, Silvia; Sterr, Michael; Burtscher, Ingo; Raducanu, Aurelia; Irmler, Martin; Beckers, Johannes; Sass, Steffen; Theis, Fabian J.; Lickert, Heiko
Abstract: Pancreas organogenesis is a highly dynamic process where neighboring tissue interactions lead to dynamic changes in gene regulatory networks that orchestrate endocrine, exocrine, and ductal lineage formation. To understand the spatio-temporal regulatory logic we have used the Forkhead transcription factor Foxa2-Venus fusion (FVF) knock-in reporter mouse to separate the FVF + pancreatic epithelium from the FVF − surrounding tissue (mesenchyme, neurons, blood, and blood vessels) to perform a genome-wide mRNA expression profiling at embryonic days (E) 12.5–15.5. Annotating genes and molecular processes suggest that FVF marks endoderm-derived multipotent epithelial progenitors at several lineage restriction steps, when the bulk of endocrine, exocrine and ductal cells are formed during the secondary transition. In the pancreatic epithelial compartment, we identified most known endocrine and exocrine lineage determining factors and diabetes-associated genes, but also unknown genes with spatio-temporal regulated pancreatic expression. In the non-endoderm-derived compartment, we identified many well-described regulatory genes that are not yet functionally annotated in pancreas development, emphasizing that neighboring tissue interactions are still ill defined. Pancreatic expression of over 635 genes was analyzed with the mRNA in situ hybridization Genepaint public database. This validated the quality of the profiling data set and identified hundreds of genes with spatially restricted expression patterns in the pancreas. Some of these genes are also targeted by pancreatic transcription factors and show active chromatin marks in human islets of Langerhans. Thus, with the highest spatio-temporal resolution of a global gene expression profile during the secondary transition, our study enables to shed light on neighboring tissue interactions, developmental timing and diabetes gene regulation. Highlights: High-resolution spatio-temporal gene expression profile of pancreas development Cell type-specific profile reveals known and many novel developmental regulators. Differential expression in pancreatic compartments reveals details about tissue interactions. In situ mRNA expression analysis validates tissue specificity and spatial expression. The established resource is of unique value to study mouse and human development and diabetes.